Pengaruh Financial Distress, Good Corporeate Govenance, Audit Report Lag dan Opini Audit Terhadap Ketepatan Waktu Publikasi Laporan Keuangan - Mukoffi, Ahmad; Sulistyowati, Yayuk; Lewa, Diana Hera (Owner : Riset dan Jurnal Akuntansi, 2024)
The purpose of this study is to determine the effect of financial distress, good corporate governance, audit report lag and audit opinion on the timeliness of financial statement publication in banking companies listed on the Indonesia Stock Exchange partially. Research conducted based on quantitative methods. The determination of this research sample used the purposive sampling method so that research samples were obtained as many as 5 state-owned banking companies listed on the Indonesia Stock Exchange. This research data uses the financial statements of banking companies for the 2018-2022 period. The data analysis method used is multiple linear regression. The results proved that financial distress had a significant effect on the timeliness of financial statement publication, good corporeate govenance had a significant effect on the timeliness of financial statement publication, audit report lag had a significant effect on the timeliness of financial statement publication and audit opinion had a significant effect on the timeliness of financial statement publication. The results together / combined obtained financial distress, good corporeate govenance, audit report lag and audit opinion have a significant effect on the timeliness of financial statement publication in banking companies listed on the Indonesia Stock Exchange with a calculated F value (4,875) or an effect of 62.5%. This result proves that the timeliness of financial statement publication is supported by low financial distress value, high good corporeate govenance, fast audit report lag and unqualified audit opinion